Mundus est Fabula: Reflections on the Nihilism of Maurice Blanchot’s “Reflections on Nihilism” - Farías Rivas, Rodrigo (Das Questões, 2020)
The article examines the importance of Nietzsche’s On the Genealogy of Morality for a formulation of nihilism and explores Blanchot’s reading of the problem.